Correction to: Effectiveness of a theory-based back care intervention on spine-related behavior among pupils: a school-based randomised controlled trial (T-Bak study) - Zahra Akbari-Chehrehbargh; Sedigheh Sadat Tavafian; Ali Montazeri (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.